Pelatihan Strategi Pemasaran Pendidikan Berbasis Digital untuk Menarik Minat Calon Orang Tua Murid di TK Islam Al-Hidayah Makassar - Nurul Chairany; Wahyuni P, Andi Dwi; Afiah, Irma Nur; Fauzan, Muh (Universitas 45 Surabaya, 2025)
Competition in the world of education is increasingly fierce, so educational institutions need to implement effective marketing strategies, even though they are not profit-oriented institutions. At the kindergarten level, increasing parental awareness of early childhood education requires institutions to offer innovative curricula, engaging learning methods, and facilities that support children's development. Al-Hidayah Islamic Kindergarten Makassar, which has been established since 1992 in Makassar, has stagnated due to a lack of innovation in its marketing strategy. Despite having quality educators and good facilities, the school lags behind its competitors because it still relies on conventional marketing methods such as word-of-mouth and banners. Therefore, a marketing strategy update is needed by utilizing information technology to be able to compete in the modern era. This community service program consists of training in marketing strategies and social media management as the main supporting facilities in marketing the school. The results of the community service activities indicate an increase in the understanding and skills of teachers and administrative staff of Al-Hidayah Islamic Kindergarten Makassar in managing social media as a bridge of information to parents and the community. The results of this PkM activity also increased the number of new student registrants in the 2025/2026 academic year.